Pengaruh Brand Image, Aktivitas Pemasaran, dan Customer Engagement di Media Sosial Terhadap Keputusan Pembelian Konsumen Pada Produk Rabbani Cabang Kopo di Bandung - Azrani, Shofia Dwi; Sarah, Siti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the influence of brand image, marketing activities, and customer engagement on social media on consumer purchasing decisions on Rabbani products, Kopo Branch in Bandung. Social media as a marketing platform has enabled Rabbani to strengthen its brand image, increase marketing activities, and build closer relationships with consumers (customer engagement). This study highlights how these three variables, both together and individually, influence consumer decisions in choosing Rabbani products. This study uses a quantitative method with a descriptive and verification approach. The researcher involved 100 respondents selected based on the Slovin formula from a total population of 28,159. The results of the descriptive test of this study indicate that brand image, marketing activities, and customer engagement are in the less good category. Brand image has a significant influence on consumer decisions to buy Rabbani products, Kopo Branch in Bandung, while marketing activities and customer engagement do not have a significant influence on consumer purchasing decisions on Rabbani products, Kopo Branch in Bandung.